Effect of a temperature rise on metal toxicity for the aquatic biota: a systematic review - Nin, Carla Juliana [UNESP]; Rodgher, Suzelei [UNESP] (Associacao Brasileira De Engenharia Sanitaria E Ambiental, 2021)
Ecosystems are subject to various stress factors, such as temperature rises due to climate changes and metal disposal. Thermal stress can amplify or mask the effects of metals on aquatic organisms. This study aims to carry out a systematic review on the effects of temperature rises due to climate changes on the toxicity of metals for freshwater organisms. Searches were made in different electronic databases and article selection was based on the following inclusion criteria: concordance with the question of a systematic review; publication in English, Spanish, and Portuguese between 1960 and 2020; and the use of standard methodology. Forty-three articles were included, which were classified with respect to the year and country of publication, test-organisms and metals studied, temperatures tested, and the effects observed. In 80% of the studies analyzed, a temperature rise was responsible for increasing the toxicity of metals for the aquatic organisms. The temperatures studied contemplated the temperature rise predicted by the Intergovernmental Panel for Climate Change at the end of the 21st century. Brazil stood out among the countries for having the greatest number of research studies in this area, although there is still the need for an increase in studies in tropical climate regions. Based on the literature review, it was shown that the metals most studied were copper and cadmium and the test-organisms most used in the research projects were fish. The information obtained from ecotoxicological studies is essential to predict the effects and prevent the risks associated with the metal contamination of aquatic ecosystems due to climate changes.
Keywords: ecotoxicology; climate changes; microalgae; zooplankton; fish